PENERAPAN AKAD SALAM DALAM JUAL BELI ONLINE PADA UNIT USAHA PERNIAGAAN KOPERASI SYARIAH BAITUL MU’MIN CILENGKRANG BANDUNG - Abdul Hakim; Rajab; Inne Risnaningsih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
This research aims to find out the Application of Salam Akad In Online Buying andSelling, Case Study on Sharia Cooperative baitul mu'min This research is conductedusing primary data, both observation and use of records and reports of Annual MemberDeliberations owned by Baitul Mu'min Sharia Cooperative. Data is obtained andanalyzed with descriptive methods with qualitative approaches. The results obtainedfrom this study whether online buying and selling using The Greeting Agreementconducted at KSBM in accordance with the Operational Standards of Salam Procedurein Baitul Mu'min Sharia Cooperative that meets the pillars and conditions, because thevalidity of buying and selling is seen from fulfilling the pillars and conditions and theexistence of willingness (anteroddin) between the two parties